A durable heterogeneous catalyst for photoinduced controlled radical polymerization under white LED light irradiation in an aqueous solution. (29th November 2022) - Yu, Chenhan; Feng, Xinyi; Li, Qiuyu; Peng, Jiahui; Xiang, Yu; Song, Yanting; Feng, Haoyu; Huang, Yunye; Xiao, Longqiang; Hou, Linxi
Abstract : An ionic heterogeneous catalyst, TD-I, was developed for the RCMP of PPEGMA in aqueous solution under white LED irradiation. Abstract : Photo-induced controlled radical polymerization (CRP) mediated by heterogeneous catalysts provides excellent spatiotemporal control and has been widely studied in view of green chemistry and potential biomedical applications. In this paper, an ionic heterogeneous catalyst (TD-I) was synthesised in a facile manner under mild conditions for inducing the reversible complexation-mediated polymerization (RCMP) of poly (polyethylene glycol monomethyl ether methacrylate) (PPEGMA) in an aqueous solution under white LED light irradiation. The obtained PPEGMA has a controllable molecular weight and a narrow molecular weight distribution. The spatio-temporal control of the catalytic system and the high chain end fidelity of the polymer have been successfully verified by on-off light experiments and chain expansion experiments. The activity and efficiency of TD-I remained essentially unchanged after being used for three cycles. Such a heterogeneous photocatalyst which can be easily separated and efficiently reused is promising for industrial applications.